EVAPORATIVE AIR COOLER THERMAL PERFORMANCE FOR RESIDENTIAL USE - da Silva, R. L.; Coca, P. H. T.; Vieira, M. M. (Revista de Engenharia Térmica, 2024)
This paper investigates an Evaporative Air Cooler (EAC) thermal performance and energy efficiency, when reducing the air temperature. EAC equipment typically consists of fan, small hydraulic pump and cooling pads. That device is able to provide ventilation only or air cooling trough water evaporative process that increases the air humidity (absolute and relative) and, as consequence, air temperature decreases (dry and wet bulb). The methodology adapts some aspects from ABNT - Brazilian Technical Standards Normative, for air conditioning devices. During tests, the fan rotor operates in 3 (three) angular speeds (RPM) in different ambient conditions for inlet air. Appropriate instrumentation and measurements registration allow to register the behavior of thermal parameters as: dry and wet bulb temperatures (Tdb and Twb, °C), air relative humidity (RH, %), enthalpy (kJ.kg-1), and water mass flow (kg.s-1). Thus, main results are for overall efficiency (η, %) considering the energy conversion from electricity to air flow hydraulic power, and cooling effectiveness (ε, %) is based on heat exchange between water evaporation and airflow rate. As main conclusions, we point out that: a) ↓Tdb for ↓mAir, reaching ΔT~5.0°C and corresponding ΔΦ~20%, when comparing outlet and inlet airflow parameters; b) EAC efectiveness reaches maximum values for lower rotor angular speeds (εEAC ~90%@1300 RPM), in comparison to higher ones; c) For a constant rotor angular speed, EAC performance (CP, εEAC and others) is strongly dependent on air ambient conditions; mAir increases from ~13.8 kg.s-1 up to ~16.5 kg.s-1 when rotor angular speeds goes from 1300 RPM to 1500 RPM.